Peningkatan Ekonomi Masyarakat Rejosari Tenayan Raya Pekanbaru, Peluang Usaha Bolu Kemojo Khas Riau Sebagai Penambah Pendapatan Ibu Rumah Tangga - fithrie, souviye; erti, lili; waldelmi, idel (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2017)
Abstract: Economic growth is one of them can be achieved by developing various potentialsof community empowerment in various economic centers in the region, which is known todevelop local culture-based economy. In developing the economic potential of local culturebased strategy is required appropriate. This strategy of economic potential developmentshould be made to look at the opportunities and potentials of a region by highlighting localadvantages and local government friendly policies. By looking at the background of problemsthat have been described above then the problem formulation of this devotion is how to createbusiness description Bolu kemojo, Product service, Operational Plan, Financing andMarketing. By paying attention to and observing the economic growth in Riau Province thenprovides an opportunity for researchers to study about mapping and strategy development oflocal culture-based economic potential in the future.